PENGEMBANGAN SISTEM PENGAJUAN UTTP DENGAN MENGGUNAKAN PROGRAM BOOTSTRAP (PHP) DALAM RANGKA PENINGKATAN DAYA SAING DAN INOVASI PADA PT KALIBRASI INDONESIA MANDIRI - Teuku Fadjar Shadek; Shodik Nuryadhin; Ainin Najmi (Program Studi Sistem Informasi, Universitas Banten Jaya, 2023)
PT Kalibrasi Indonesia Mandiri is one unit of the legal metrology agency in Serang Regency that functions are to control, manage and determine the types of measuring instruments, scales and equipment (UTTP) by setting mass standards, volume standards and length standards. PT Kalibrasi Indonesia Mandiri is under department of Industry, Trade, Cooperatives and SMEs in Banten province, as one of the Technical Implementation Unit (UPT). In accepting UTTP (Measuring, Measure, Weighing, and Equipment) submissions from institutions or companies is still manual and there is no system. For this reasons, the author was designed a system to facilitate the processing of UTTP submissions received at the Technical Implementation Unit in a systemized (online) manner. The solution is using a web-based application. For this reason the author choose the title